Developing the Lex Mercatoria - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2023)
The historical lex mercatoria, or law merchant, is said to have emerged from the customary practices of ancient and medieval seamen and traders who found themselves in need of a common set of rules to govern mercantile trade; rules which would be broadly applicable (and acceptable) to trading parties regardless of their places of origin. To the extent that such a body of legal rules did in fact exist, its significance derived from two main features: (1) its independence (since it was not promulgated by any one decision-maker or legislator, but was drawn from the established practice of the merchant community); and (2) relatedly, its practical utility and credibility (as a set of rules which were created in the marketplace and therefore reflected the actual practices and needs of those subject to it).